2010
DOI: 10.1161/strokeaha.109.572594
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic Drug Use, Cerebral Microbleeds, and Intracerebral Hemorrhage

Abstract: Background and Purpose-Cerebral microbleeds (MB) are potential risk factors for intracerebral hemorrhage (ICH), but it is unclear if they are a contraindication to using antithrombotic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
144
3
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(162 citation statements)
references
References 31 publications
(51 reference statements)
4
144
3
8
Order By: Relevance
“…The population‐based Rotterdam Scan study found that antiplatelet agent was related to the presence of CMBs, but anticoagulation was not (Darweesh et al., 2013; Vernooij et al., 2009). A systematic review including ICH and ischemic stroke/TIA found that both antiplatelet and warfarin were associated with presence of CMBs (Lovelock et al., 2010). In contrast, a study with asymptomatic elderly subjects showed no significant association of antithrombotic therapy with CMBs (Kim, Kwon, & Kwon, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The population‐based Rotterdam Scan study found that antiplatelet agent was related to the presence of CMBs, but anticoagulation was not (Darweesh et al., 2013; Vernooij et al., 2009). A systematic review including ICH and ischemic stroke/TIA found that both antiplatelet and warfarin were associated with presence of CMBs (Lovelock et al., 2010). In contrast, a study with asymptomatic elderly subjects showed no significant association of antithrombotic therapy with CMBs (Kim, Kwon, & Kwon, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the literature reviewed in this article, ischemic stroke occurred frequently in patients with giant aneurysms, and this must be considered during the period of postoperative medication. In addition, as the intracranial hemorrhage rate is known to be high in patients showing microbleeds on MRI, 19,20) MRI should be performed preoperatively, and the findings should be taken into consideration in evaluating the indications. Flow diverters have been used in many patients with large/giant cerebral aneurysms primarily in Western countries and have also been introduced to Japan with high expectations.…”
Section: Meta-analysismentioning
confidence: 99%
“…There is a potential for severe bleeding (including IPH) with therapeutic anticoagulation, even with the international normalized ratio (INR) in the goal range. An increased risk for microbleeds is seen with warfarin, and may presage an increased risk for symptomatic IPH (19). As the intensity of anticoagulation increases, so does the risk for IPH (18,20).…”
Section: Intracranial Hemorrhage During Medical Treatmentmentioning
confidence: 99%